Efficacy of mesoporous TiO2–ZrO2@g-C3N4 produced using a simple ultrasonic approach for copper ion removal from wastewater - B.A. El-Badry; O. Aldaghri; K.H. Ibnaouf; Alaa M. Younis; Abuzar Albadri; Abdullah H. Alluhayb; Mohamed Ali Ben Aissa; A. Modwi (Journal of Science: Advanced Materials and Devices)
The present study describes ultrasonically produced ternary composite material composed of carbon nitride nanosheets, zirconium, and titanium oxides for elimination of copper ions. The formation of monoclinic ZrO2, anatase TiO2, and g-C3N4 phases with respective crystallite sizes 6, 11, 13 nm were verified by the X-ray diffraction technique. The dispersion of the metal oxides nanoparticles with the graphitic nanosheets, the elemental composition of Zr, Ti, O, C and N, and the characteristic functional groups were verified respectively by TEM, EDX, and FTIR analysis that confirmed the successful formation and composition of the nanocomposite TiO2–ZrO2@g-C3N4 (TZCN). The good porosity of the composite that show a surface area, pore volume, and pore diameter values of 47.42 m2/g, 0.056 cm3 g−1, and 20.3 Å that nominate it for adsorption application. The adsorption capabilities of the nanocomposite were studied for copper ion removal from an aqueous solution, as well as the impacts of pH and starting Cu2+ concentration. The results show that the adsorption process is pH and starting concentration-dependent, with a maximum adsorption capacity of 447.8 mg/g. The Cu2+ adsorption is a monolayer chemisorption process that is well described by the Langmuir adsorption model and follows pseudo-second-order kinetics. Moreover, a plausible mechanism for Cu2+ ion adsorption on the surface of TZCN nanocomposite particles is proposed.